Assessing transplant representation: psychometric characteristics of the Transplanted Organ Questionnaire in an Italian sample of transplant recipients - Benedetta Muzii; Emmanuelle Corruble; Francesco Palumbo; Giorgia Margherita (Mediterranean Journal of Clinical Psychology, 2023)
Background: Organ transplantation may elicit several emotional responses, where the lack of psychological integration of the allograft can lead to up to out-to-out manifestations of psychopathological symptoms. As there are only a few studies which examined the impact of a successful psychological integration, it is mandatory to have a specific tool available. The aim of this study is to assess the factorial structure of the Italian translation of the Transplanted Organ Questionnaire (TOQ) and verify the association with its dimensions and psychopathology.